Latent and Affine Subsystems of Reference-Bibliographical Tools of Library - Shkarina Vitalina (Bìblìotečnij vìsnik, 2017)

(untitled)
Article outlines approaches to determination of the structure of reference-bibliographical tools of library as a system, a value opens up for his valuable functioning of latent and affine bibliographic information.